Electrocatalysts: In Situ Synthesis of MoP Nanoflakes Intercalated N‐Doped Graphene Nanobelts from MoO3–Amine Hybrid for High‐Efficient Hydrogen Evolution Reaction (Small 25/2018). Issue 25 (21st June 2018) - Huang, Chao; Pi, Chaoran; Zhang, Xuming; Ding, Kang; Qin, Ping; Fu, Jijiang; Peng, Xiang; Gao, Biao; Chu, Paul K.; Huo, Kaifu
Abstract : In article number 1800667, Xuming Zhang, Kaifu Huo, and co‐workers fabricate alternatingly stacked Molybdenum phosphide (MoP)/nitrogen‐doped graphene hybrid nanobelts by a one‐step thermal phosphiding organic–inorganic hybrid, which provides abundant edge sites on the MoP nanoflake and rapid ion/electron transport, thus yielding excellent electrochemical activity and stability for high performance hydrogen evolution reaction.